Integrasi Nilai-Nilai Budaya Lokal dalam Civics Education Curriculum: Upaya Menumbuhkan Kesadaran Multikultural Peserta Didik - Ardiansyah, Suriadi; Yorman; Felia Siska (Universitas Negeri Semarang, 2025)
This study aims to critically examine the integration of Sasak local cultural values into the Civic Education curriculum as a pedagogical strategy to foster students’ multicultural awareness at State Junior High School 1 Aikmel, East Lombok, West Nusa Tenggara. The local culture of the Sasak was selected due to its rich philosophical values that reflect social, religious, economic, aesthetic, political, and power dimensions making it highly relevant to character education. A descriptive qualitative method with an ethnographic approach was employed. Data were collected through participatory observations, in-depth interviews with teachers, students, and cultural figures, and documentation of traditional practices still preserved in the community. The findings reveal that local cultural values embedded in traditions such as srakala (birth ritual), besiru (social cooperation), drum beleq (traditional music), teacher (leadership figure), and paresean (symbol of strength and courage) can be contextually integrated into Civic Education materials. This integration makes learning more innovative, relevant, and meaningful, enabling students to grasp civic concepts in practical and experiential ways. Moreover, the approach cultivates students' character, particularly in tolerance, mutual respect, and openness toward cultural diversity. Learning grounded in local cultural values also enhances students’ active participation and nurtures democratic and inclusive classroom dialogue. In conclusion, integrating local cultural values into Civic Education is a strategic and innovative effort that not only builds multicultural awareness but also reinforces local identity and improves the quality of character education in a pluralistic and dynamic society.